Total serum IgE levels in soil-transmitted helminth infected children with atopy symptoms - Hendri Wijaya; Lily Irsa; Supriatmo Supriatmo; Sjabaroeddin Loebis; Rita Evalina (Indonesian Pediatric Society, 2014)
Background High total serum immunoglobulin E (IgE) levelsand eosinophilia are markers for atopy, but other factors mayalso play a key role in affecting atopy, such as intestinal parasiticinfection. Helminthiasis has been associated with a reduced riskof atopy and asthma symptoms in areas with high prevalence ofparasitic infections.Objective To assess for associations between total serum IgElevel and soil-transmitted helminthiasis (STH) infection, as wellas between STH infection and allergy symptoms.Methods We conducted a cross-sectional stu dy on 84consecutively-enrolled children , aged 7- 13 years, in theSecanggang Subdistrict, Langkat District, North SumateraProvince. Subjects were enrolled into one of two groups, with orwithout STH infection. Total serum IgE measurements and stoolSTH examinations were performed in all subjects. Data on atopyor allergy symptoms were obtained by parental interview.Results The 42 subjects with STH infection had significantlyhigher mean total serum lg E levels than the 42 subjects withoutinfec tion, 1,13 1.26 IU/mL and 744.76 IU/mL, respectiv ely(P = 0.029). We also fo und significant positive association sbetween STH infection and asthma symptoms (P= 0.049), as wellas eczema symptoms (P=0.044).Conclusion Mean total serum IgE level is higher in STHinfectedsubjects than in those without infection. In addition,STH infection is positively associated with asthma and eczemasymptoms.